A research on the change of finger temperatures of junior table tennis athletes at pre-match - Cheng, Y. F. (2001)
Before a match or during training a number of changes occur in the human body. One of these is a change in the temperature of the fingers in the athletes. In this study the finger temperatures of 16 elite table tennis athletes were measured before matches. The finger temperatures of the hand holding a bat and the hand without were compared. These temperatures were also compared with that of ordinary athletes. The mechanism and significance of finger temperature change were discussed. Results were as follows: 1. In elite athletes, the finger temperatures of the hands with the bat were significantly higher. 2. In students majoring table tennis in a sport college. The finger temperatures were also higher in the hands with bats. However, the difference was not as statistically significant. Hence the temperature changes at prematch can be regarded as a simple and useful index and can be used as a reference.